STUDI KERAGAMAN DAN KERAPATAN NEMATODA PADA BERBAGAI SISTEM PENGGUNAAN LAHAN DI SUB DAS KONTO - Liliana Sagita; Bambang Siswanto; Hairiah Kurniatun (Jurnal Tanah dan Sumberdaya Lahan, 2014)
Maintaining litter thickness on agricultural land is one of key factor for maintaining diversity of nematode. Litter on soil surface is energy source of decomposer which will be consumed by bacterivore nematode. Higher litter input gives benefit to crop through maintaining diversity of non parasite nematode, improving soil porosity and soil moisture which important to control plant parasite nematode and achieve a sustainable crop production. The research was conducted to study diversity and abundance of nematodes in various landuse system and effect of different soil temperature and water content of various landuse system to nematode`s diversity and it`s abundance. Soil sampling on nine landuse system (degraded forest, bamboo forest, coffee multistrate, Gliricidia shade coffee, mahoghany plantation, pine plantation, Aghatis plantation, grassland and annual crop). Nematodes were extracted by sieving-centrifugation with sugar method. The soil nematodes were grouped into order and generic level including plant parasitic and non-paracitic. The result show that the diversity (number of taksa) and abundance of soil nematode in Konto watershed were high with a total of 44 taksa nematode genera and a total number ranged 334-910 individuals/300 cc of soil. The nematode`s diversity was decreased from 44 genera in degraded forest to 24 genera in Gliricidia shade coffee. The diversity and abundance of nematodes was not linked to variation of water content, but were correlated to plant vegetation and clay content. Diversity of Free-living nematodes was closely correlated with plant diversity (R2 = 0,69) and litter biomass (R2 = 0,32). While plant parasitic nematodes was closely correlated and significant with clay content (R2 = 0,62).Key words: nematodes, diversity, landuse system